The effect of presence of midwife (Doula) on anxiety and fear of natural childbirth in pregnant women: Randomized Clinical Trial - Sedigheh Khalili Shomia; Farzaneh Khodabandeh; Fatemeh Borzoee; Ellahe Bahrami Vazir; Elham Navipour; Bita Koushki (Mashhad University of Medical Sciences, 2022)
Introduction: Anxiety and fear of childbirth is one of the biggest concerns of pregnant women that may lead to the pain and prolonged delivery. Regarding to the midwives' treatment and supportive roles, this study was performed aimed to evaluate the effect of the presence of doula on the fear and anxiety of natural childbirth in pregnant women. Methods: This randomized clinical trial study was conducted in 2018 on 80 pregnant women in the Hakim Hospital, Neishabour. In the intervention group, doula was with the women from the beginning of labor until one hour after the placenta was removed, doula performed supportive measures for them. But the control group received only routine care. In both groups, the Hamilton Anxiety Rating Scale and the Hartmann Childbirth Attitude Questionnaire were completed in three stages. Data were analyzed by SPSS software (version 20) and Independent t-test, chi-square, analysis of variance with repeated measures. p>0.05 was considered statistically significant. Results: There were no significant differences between the two group regarding individual socio-demographic, midwifery, the mean score of anxiety and fear of childbirth at the time of entering the delivery ward (P>0.05). The presence of a doula significantly reduced the mean score of anxiety and fear of childbirth in the active phase of labor and one hour after placental remove in the intervention group compared with the control group (P<0.001). Conclusion: The presence of doula in the delivery wards as a simple and non-invasive intervention can reduces anxiety and fear of natural childbirth in pregnant women.